2010
DOI: 10.4137/jcnsd.s4886
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Enacarbil: Pharmacotherapy of Restless Legs Syndrome

Abstract: Restless Legs Syndrome (RLS) is a prevalent sleep-associated movement disorder greatly affecting patients’ quality of life (QoL). Several drugs can be used to control this condition although the first-line dopamine agents often cause adverse effects. Non-dopaminergic drugs such as oral gabapentin (GBP) have been more recently advocated. Despite ameliorating RLS symptoms, GBP’s pharmacokinetic limitations restrict its overall effectiveness. A novel specifically designed prodrug, gabapentin enacarbil (GE), has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that sufferers experiencing painful symptoms or neuropathy should receive anticonvulsants as firstline treatment [10]. Gabapentin Enacarbil (GE), a prodrug of GBP, has recently demonstrated effectiveness in RLS and could be a potentially useful therapeutic option [43].…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…It has been suggested that sufferers experiencing painful symptoms or neuropathy should receive anticonvulsants as firstline treatment [10]. Gabapentin Enacarbil (GE), a prodrug of GBP, has recently demonstrated effectiveness in RLS and could be a potentially useful therapeutic option [43].…”
Section: Anticonvulsantsmentioning
confidence: 99%